2023
DOI: 10.1021/acsomega.3c01455
|View full text |Cite
|
Sign up to set email alerts
|

20-State Molecular Switch in a Li@C60 Complex

Abstract: A substantial potential advantage of industrial electric and thermoelectric devices utilizing endohedral metallofullerenes (EMFs) is their ability to accommodate metallic moieties inside their empty cavities. Experimental and theoretical studies have elucidated the merit of this extraordinary feature with respect to developing electrical conductance and thermopower. Published research studies have demonstrated multiple state molecular switches initiated with 4, 6, and 14 distinguished switching states. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Next we consider the electrical conductance when electrodes are connected to thiols 1 and 4 or 2 and 3. Since the 1-4 path includes ortho 'a'-'c' and ortho 'd'-'f', we To examine the above quantum interference predictions, we construct a Hu ¨ckel (i.e., tight binding, TB) Hamiltonian, [26][27][28][29][30][31][32][33][34][35][36][37] which captures the dependence of the conductance for the two cross-linked dimers on their connectivity to electrodes. The Hamiltonian matrix comprises of diagonal elements H jj = e j , which describe the energy e j of an electron on site j and nearest neighbour off-diagonal elements H ij , which describe hopping integrals between neighbouring sites l and j.…”
Section: Methodsmentioning
confidence: 99%
“…Next we consider the electrical conductance when electrodes are connected to thiols 1 and 4 or 2 and 3. Since the 1-4 path includes ortho 'a'-'c' and ortho 'd'-'f', we To examine the above quantum interference predictions, we construct a Hu ¨ckel (i.e., tight binding, TB) Hamiltonian, [26][27][28][29][30][31][32][33][34][35][36][37] which captures the dependence of the conductance for the two cross-linked dimers on their connectivity to electrodes. The Hamiltonian matrix comprises of diagonal elements H jj = e j , which describe the energy e j of an electron on site j and nearest neighbour off-diagonal elements H ij , which describe hopping integrals between neighbouring sites l and j.…”
Section: Methodsmentioning
confidence: 99%
“…We used a double-zeta plus polarization orbital basis set, norm-conserving pseudopotentials, the local density approximation (LDA) exchange-correlation functional, and an energy cutoff of 250 rydbergs to define the real space grid. We also computed the results using the generalized gradient approximation (GGA) and found that the resulting transmission functions were comparable [30][31][32][33] to those obtained using LDA. To simulate the likely contact configuration during a break-junction experiment, we used leads constructed from six layers of PAHs.…”
Section: Resultsmentioning
confidence: 94%
“…In this study, it was shaped into a cone-shaped tip, and the tip retained its shape due to the formation of a ∼0.7 nm native oxide outer shell (GaOx) upon contact with air. 49,50 It has been proved that this type of tip can contact non-destructively with SAMs4, 8–52 and form Cu/Gr/SAMs/GaOx/EGaIn junction.…”
Section: Introductionmentioning
confidence: 95%
“…[7][8][9] The electric and thermoelectric properties of molecular junctions have been extensively investigated in recent years, both at the level of individual molecules [10][11][12][13] and self-assembled monolayers (SAMs). [14][15][16] These studies have predominantly focused on noble-metal substrates like gold, silver, and platinum, together with organic molecular backbones, with specific anchor groups, such as thiolate, [17][18][19] pyridine, fullerene, 20,21 and large p systems. 22,23 These anchor groups bind to a metallic substrate and facilitate the spontaneous formation of molecular layers on the substrate.…”
Section: Introductionmentioning
confidence: 99%